2014
DOI: 10.1007/s00049-014-0180-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of male-borne attractants in Anastrepha fraterculus (Diptera: Tephritidae)

Abstract: The South American fruit fly is one of the most destructive polyphagous pests in South America. In this species, males gathered in aggregations emit volatiles that attract females; however, the compounds involved in this task remain unknown. In this study, we investigated the chemical composition of the volatile blend emitted by males aiming to identify the specific compounds within this blend that elicit behavioral responses in conspecific females. For this purpose, we performed chemical and electrophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 22 publications
(33 reference statements)
0
40
0
1
Order By: Relevance
“…In addition, females from the different morphotypes showed differences in their antennal response (Břízová et al 2013, Milet-Pinheiro et al 2014), i.e. while the antenna of Tucumán, Argentina (Brazilian-1 morphotype) females responded to ( Z , E )-a-Farnesene, ( E , E )-a-Farnesene, Epianastrephin, ( Z )-3-Nonen-1-ol and ( E , Z )-3,6-Nonadien-1-ol (Břízová et al 2013), the antenna of Alagoas (Brazilian-3 morphotype) females responded to a- Pinene, Limonene, ( Z )-3-Nonen-1-ol and ( E , Z )-3,6-Nonadien-1-ol, (S,S)-(-)-Epianastrephin (Milet-Pinheiro et al 2014).…”
Section: The Role Of Pheromones In Species Recognitionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, females from the different morphotypes showed differences in their antennal response (Břízová et al 2013, Milet-Pinheiro et al 2014), i.e. while the antenna of Tucumán, Argentina (Brazilian-1 morphotype) females responded to ( Z , E )-a-Farnesene, ( E , E )-a-Farnesene, Epianastrephin, ( Z )-3-Nonen-1-ol and ( E , Z )-3,6-Nonadien-1-ol (Břízová et al 2013), the antenna of Alagoas (Brazilian-3 morphotype) females responded to a- Pinene, Limonene, ( Z )-3-Nonen-1-ol and ( E , Z )-3,6-Nonadien-1-ol, (S,S)-(-)-Epianastrephin (Milet-Pinheiro et al 2014).…”
Section: The Role Of Pheromones In Species Recognitionmentioning
confidence: 99%
“…In addition, females from the different morphotypes showed differences in their antennal response (Břízová et al 2013, Milet-Pinheiro et al 2014), i.e. while the antenna of Tucumán, Argentina (Brazilian-1 morphotype) females responded to ( Z , E )-a-Farnesene, ( E , E )-a-Farnesene, Epianastrephin, ( Z )-3-Nonen-1-ol and ( E , Z )-3,6-Nonadien-1-ol (Břízová et al 2013), the antenna of Alagoas (Brazilian-3 morphotype) females responded to a- Pinene, Limonene, ( Z )-3-Nonen-1-ol and ( E , Z )-3,6-Nonadien-1-ol, (S,S)-(-)-Epianastrephin (Milet-Pinheiro et al 2014). Although it has been shown that these compounds attracted females of the Brazilian-3 morphotype and that the females responded equally to an artificial blend of the synthetic compounds and to volatiles collected from males, it is still not known whether these differences observed at the chemical and electrophysiological level are translated into different behaviors, since the behavioral response to the pheromone of the Argentinean populations is not known yet.…”
Section: The Role Of Pheromones In Species Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many volatiles identified in Ceratitis FAR male emanation have been previously identified in other tephritid pheromones (Cruz-López et al 2006, Heath et al 1991, Lu and Teal 2001, Milet-Pinheiro et al 2014, Robacker 1988, Rocca et al 1993, Vaníčková 2012, Vaníčková et al 2012). Others, specifically isoprenoid geranyl acetone, aliphatic volatile ( E )-non-2-enal, and methyl (2 E ,6 E )-farnesoate, have not been reported before.…”
Section: Resultsmentioning
confidence: 83%